A proposed model for green practice adoption and implementation in information technology based organizations - Anthony, Bokolo Jnr.; Mazlina, Abdul Majid; Awanis, Romli (Politechnika Lubelska, 2018)
Green Information technology system offers opportunity for IT based organizations to act proactively in terms of environmental preservation as well as to mitigate effects of global climate change and other environmental problems. Green Information technology system adoption and implementation is a plausible attempt for IT based organizations to resolve the current environmental issues and also enhance their economic performance and possible social benefits. Currently several models and frameworks have been developed to address sustainability in various research domain. However, there are few models that can support decision making of practitioners in adopting and implementing sustainable practices in IT based organization. Therefore there is need to develop a model to assist practitioners adopt and implement sustainable practices. The proposed model comprises of Green variables, Green process and a hybrid technique of software agents and case bases reasoning. Findings from this paper shows the model variables, process, techniques applied and derived prepositions. Ongoing work involves adopting a mixed research (case study and survey) to verify the model variables, process and validate the model prepositions.